APPLICATION OF ONLINE DISPUTE RESOLUTION (ODR) IN THE ELECTORAL JUSTICE SYSTEM: PATHWAYS TO MODERNIZATION IN LIGHT OF CNJ RESOLUTION Nº 358/2020 - Coelho Nunes Campos, Débora; Aguiar de Alencar, Kalyne Laura; Brito Alves Sabino, Luis Fernando; Barros Sales, Teresa Helena (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
This study examines the potential application of Online Dispute Resolution (ODR) as a tool for modernizing the Brazilian Public Administration, given the advancement of digital technologies and the growing volume of conflicts arising from political interactions in virtual environments. Considering that democratic legitimacy depends on swift, secure, and accessible mechanisms for handling electoral disputes, the research seeks to understand how CNJ Resolution Nº. 358/2020, which establishes the National Judicial Policy for the appropriate treatment of conflicts through technological means, can inspire innovative practices in the administrative sphere, respecting its constitutional autonomy, hybrid structure, and procedural peculiarities. The methodological approach is qualitative, descriptive, and exploratory, based on a literature review and documentary analysis of regulations, doctrine, and international experiences of ODR. Initially, the conceptual and normative foundations of ODR are presented, as well as the principles that guide its operation, such as efficiency, access to justice, data protection, and legal certainty. Next, the structure and contemporary challenges of the Electoral Justice system are analyzed, especially in light of the intensification of demands related to digital propaganda, disinformation, intra-party conflicts, and administrative issues. Finally, the feasibility of implementing ODR models for the adequate handling of these disputes is discussed, evaluating benefits, risks, limitations, and guidelines for its progressive adoption. It is concluded that, despite challenges such as digital exclusion, the need for institutional capacity building, and information security safeguards, ODR has the potential to contribute significantly to the efficiency, transparency, and accessibility of the Electoral Justice system, establishing itself as a strategic vector of democratic innovation.